Empowering Communities through Culinary Innovation: Enhancing Nutritional Status in Toddlers with Tempe-Based Supplementary Foods - Hikmawati, Hanifah; Sutami, Sutami (Communautaire: Journal of Community Service, 2024)
This study focuses on evaluating the effectiveness of tempe-based culinary training programs in improving the nutritional status of toddlers and empowering the local economy in Jati Sumberlawang village, Indonesia. The main objective of this research is to identify how tempe, a locally available and nutritious food, can be optimized as a supplementary food (PMT) to address malnutrition among toddlers while also providing economic benefits to the community. A qualitative research method with a case study approach was employed, involving in-depth interviews, participant observations, and documentation analysis. Data were collected from 20 mothers who participated in the training and were analyzed using thematic analysis to identify key patterns and outcomes. The results indicate a significant improvement in the mothers' knowledge and skills in processing tempe into various child-friendly dishes, which led to increased acceptance and consumption among toddlers. Additionally, some participants began commercializing tempe-based products, leading to increased household income. The implications of this study suggest that community-based culinary training can serve as an effective model for improving child nutrition and promoting local economic development. This research highlights the potential for replicating similar programs in other rural communities facing similar nutritional challenges.